An Evaluation of the Performance of Forced Air Cooling on Cooling Parameters in Transient Heat Transfer at Different Layers of Pomegranate - Mohammad-ali Behaeen; Asgar Mahmoudı; Seyed-faramarz Ranjbar (Journal of Agricultural Sciences)
The quality of horticultural products can be promoted using high techniques. One of these methods is precooling applied before storage and leads to increased shelf and storage life of the fruit. For this reason, the effect of forced air cooling was conducted to investigate the cooling rate at the center (aril), spongy tissue (peel) and leathery skin (rind) of pomegranate (Punica granatum L.). Airflow velocity as an effective factor in cooling products at three levels of 0.5, 1, and 1.3 m s-1 and temperature of 7.2 °C was considered. Cooling parameters including lag factor and cooling coefficient were calculated from experimental data. Then, half-cooling time and seven-eighths cooling time were obtained at different layers of pomegranate. Cooling heterogeneity was analyzed at different air velocity and at different layers of pomegranate. The results showed that increase in air velocity from 0.5 to 1.3 m s-1, reduced the half-cooling time and seven-eighths cooling time. After 5000 seconds, the change of air velocity had a slight influence on decreasing temperature of different layers of pomegranate. Cooling heterogeneity at the air velocity of 0.5 m s-1 was low and then increased at the air velocity of 1 m s-1. Finally, at the air velocity of 1.3 m s-1, it was declined. The overall results illustrate that the applied methodology in this research, which explains unsteady heat transfer in the cooling process, can be performed in pomegranate or similarly shaped fruits.